Development and Validation of UV Spectrophotometric Method for the Determination of Cefuroxime Axetil in Bulk and Pharmaceutical Formulation (Journal of Scientific Research, 2013)
The present study was undertaken to develop and validate a simple, sensitive, accurate, precise and reproducible UV spectrophotometric method for cefuroxime axetil using methanol as solvent. In this method the simple UV spectrum of cefuroxime axetil in methanol was obtained which exhibits absorption maxima (?max) at 278 nm. The quantitative determination of the drug was carried out at 278 nm and Beers law was obeyed in the range of (0.80-3.60) µg/ml. The proposed method was applied to pharmaceutical formulation and percent amount of drug estimated (95.6% and 96%) was found in good agreement with the label claim. The developed method was successfully validated with respect to linearity, specificity, accuracy and precision. The method was shown linear in the mentioned concentrations having line equation y = 0.05x + 0.048 with correlation coefficient of 0.995. The recovery values for cefuroxime axetil ranged from 99.85-100.05. The relative standard deviation of six replicates of assay was less than 2%. The percent relative standard deviations of inter-day precision ranged between 1.45-1.92% and intra-day precision of cefuroxime axetil was 0.96-1.51%. Hence, proposed method was precise, accurate and cost effective.  Keywords: UV-Vis spectrophotometer; Method validation; Cefuroxime axetil; Recovery studies.  © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved.   doi: http://dx.doi.org/10.3329/jsr.v6i1.14879 J. Sci. Res. 6 (1), 133-141 (2013)